Population dynamics of Zeuzera spp. (Lepidoptera: Cossidae) on Eucalyptus pellita plantation in Central Kalimantan, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Suheri M, Haneda NF, Anwar R, Jung Y, Sukeno S, Park J. 2022. Population dynamics of Zeuzera spp. (Lepidoptera: Cossidae) on Eucalyptus pellita plantation in Central Kalimantan, Indonesia. Biodiversitas 23: 5782-5789. The red coffee borer, Zeuzera spp. (Lepidoptera: Cossidae) damage to Eucalyptus pellita forests was one of the problems in the forestry sector. The population dynamic of these insects is monitored and surveyed on E. pellita at PT Korintiga Hutani. The present study aimed to analyze the contributing factors of Zeuzera spp. damage to E. pellita plantation and observe the population dynamics of Zeuzera spp. using pheromone traps. The survey results showed that the accumulated damage in planting block 5 was more serious (29%) than in planting block 6 (9%). The impact of the multi-regression analysis indicates that the main factors affecting the damage are the location and age of the plantation. At the same time, the E. pellita clonal difference is minor compared to those two factors. The damage is more severe and occurs at an older age of plantations. The population dynamics of Zeuzera spp. observed in E. pellita plantation showed a peak flight trend in October, followed by a reasonably high population presence from late May to early June. This information could be a primary consideration for these insect pest need to control the significant damage to E. pellita trees and determine the management of Zeuzera spp. based on the timing of larvae infestation in the upcoming after-peak flight.